Sintering of calcium phosphates with a femtosecond pulsed laser for hard tissue engineering. (5th July 2016) - Anastasiou, A.D.; Thomson, C.L.; Hussain, S.A.; Edwards, T.J.; Strafford, S.; Malinowski, M.; Mathieson, R.; Brown, C.T.A.; Brown, A.P.; Duggal, M.S.; Jha, A.
Abstract: Direct laser sintering on hard tissues is likely to open new pathways for personalised medicine. To minimise irradiation damage of the surrounding soft tissues, lasers operating at wavelengths that are 'safe' for the tissues and biomaterials with improved optical properties are required. In this work laser sintering is demonstrated with the use of an ultrafast, femtosecond (100 fs) pulsed laser operating at a wavelength of 1045 nm and two existing calcium phosphate minerals (brushite and hydroxyapatite) which have been improved after doping with iron (10 mol%). Femtosecond laser irradiation caused transformation of the Fe 3 + -doped brushite and Fe 3 + -doped HAp samples into β-calcium pyrophosphate and calcium-iron-phosphate, respectively, with simultaneous evidence for microstructural sintering and densification. After estimating the temperature profile at the surface of the samples we suggest that soft tissues over 500 μm from the irradiated zone would be safe from thermal damage. This novel laser processing provides a means to control the phase constitution and the morphology of the finished surfaces. The porous structure of β-pyrophosphate might be suitable for applications in bone regeneration by supporting osteogenic cell activity while, the densified Fe 3 + -rich calcium-iron-phosphate may be promising for applications like dental enamel restoration. Graphical abstract: Highlights: Sintering of calcium phosphate materials with a femtosecond laser is demonstrated. Irradiation conditions safe for the soft tissues have been used. Iron doped biomaterials with improved optical properties have been designed. Iron doping found to enhance laser sintering. Heat dissipation graph indicates very localised temperature rise.